2006
DOI: 10.1007/s00259-006-0113-7
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-EDDA/HYNIC-octreotate scintigraphy, an efficient method for the detection and staging of carcinoid tumours: results of 3 years’ experience

Abstract: 99mTc-EDDA/HYNIC-octreotate, with high imaging quality, is an excellent alternative to 111In-Octreoscan for staging of carcinoids, and it seems to be the method of choice for detection of the primary focus in patients with metastases from an unknown primary tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 27 publications
5
52
0
2
Order By: Relevance
“…Tc-EDDA/HYNIC-TOC SPECT and whole body scintigraphy for detecting primary lung NETs or lung metastases is in agreement with previous reports [14,15]. Several factors may be responsible for our FN findings, such as an insufficient expression of SSTR2 for in-vivo detection by 99m Tc-EDDA/HYNIC-TOC or a comparably higher expression of other SSTR subtypes (SSTR3, SSTR4 or SSTR5) in our cases with low-differentiated tumors.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Tc-EDDA/HYNIC-TOC SPECT and whole body scintigraphy for detecting primary lung NETs or lung metastases is in agreement with previous reports [14,15]. Several factors may be responsible for our FN findings, such as an insufficient expression of SSTR2 for in-vivo detection by 99m Tc-EDDA/HYNIC-TOC or a comparably higher expression of other SSTR subtypes (SSTR3, SSTR4 or SSTR5) in our cases with low-differentiated tumors.…”
Section: Discussionsupporting
confidence: 82%
“…Semiquantitative results in our study confirm previously reported higher T/NT ratios on SPECT than whole body images [9,15]. As expected, therefore, SPECT should be preferred over whole body scintigraphy as it can more precisely detect and localize focal lung lesions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…26 There is also evidence to suggest that octreotide scans are useful in occult ACTH-secreting tumors, including those of bronchial origin. [26][27][28] …”
Section: Presentationmentioning
confidence: 99%
“…These tests can identify lesions undetected by anatomical imaging methods, increasing the chances of locating the primary focus and determining the actual stage of the neoplasm [6,[107][108][109]. They may also be the firstline method in the diagnostics of early recurrence, in monitoring the disease, and in choosing a suitable treatment.…”
Section: Radioisotope Diagnostics Of Pnensmentioning
confidence: 99%